Differences between the Maxilla Canine Index and the Mandibular Canine Index in Preclinical Students at the Faculty of Dentistry, Yarsi University, Jakarta - mart shelina gaman; Okky Marita Ardy; Djuned Prasonto (YARSI Dental Scientific Meeting - e Journal, 2026)
Background: This study aims to analyze the differences in Maxilla Canine Index (MxCI) and Mandibular Canine Index (MCI) in preclinical students of the Faculty of Dentistry, YARSI University, and explore the Islamic perspective on its use in forensic identification. Method: A descriptive observational method with a crosssectional approach was used in 115 samples (18 males, 97 females). Measurements were performed on dental models using digital calipers, followed by univariate and bivariate analysis with the Mann-Whitney U test due to the non-normal distribution of data in the female group. Result: The results showed a mean value of MxCI of 0.498 (SD 0.124) and MCI of 0.528 (SD 0.085). There was no significant difference between MxCI and MCI between genders (p MxCI=0.568; p MCI=0.614). Descriptively, females' scores were slightly higher, likely due to sample imbalance and external factors such as nutrition. Conclusion: The MxCI and MCI are not sensitive enough as sole indicators of sexual dimorphism in this population, requiring a combination of other methods..